Lived Religion and Everyday Life in Early Modern Hagiographic Material
XII, 328 p. 14 illus.
Keywords: This book discusses the ways in which early modern hagiographic sources can be used to study lived religion and everyday life from the fifteenth to the seventeenth century. For several decades, saints’ lives, other spiritual biographies, miracle narratives, canonisation processes, iconography, and dramas, have been widely utilised in studies on medieval religious practices and social history. This fruitful material has however been overlooked in studies of the early modern period, despite the fact that it witnessed an unprecedented growth in the volume of hagiographic material. The contributors to this volume address this, and illuminate how early modern hagiographic material can be used for the study of topics such as religious life, the social history of medicine, survival strategies, domestic violence, and the religious experience of slaves.